Predicting orogenic wedge styles as a function of analogue erosion law and material softening. (7th October 2013) - Mary, Baptiste C. L.; Maillot, Bertrand; Leroy, Yves M.
<x xml:space="preserve">Abstract</x> [1] The evolution of a compressive frictional wedge on a weak, frictional and planar décollement, subjected to frontal accretion, is predicted with a two step method called sequential limit analysis. The first step consists in finding, with the kinematic approach of limit analysis, the length of the active décollement and the dips of the emerging ramp and of the conjugate shear plane composing the emerging thrust fold. The second step leads to a modification of the geometry, first, because of the thrust fold development due to compression and, second, because of erosion. Erosion consists in removing periodically any material above a fictitious line at a selected slope, as done in analogue experiments. This application of sequential limit analysis generalizes the critical Coulomb wedge theory since it follows the internal deformation development. With constant frictional properties, the deformation is mostly diffuse, a succession of thrust folds being activated so that the topographic slope reaches exactly the theoretical, critical value. Frictional weakening on the ramps results in a deformation style composed of thrust sheets and horses. Applying an erosion slope at the critical topographic value leads to exhumation in the frontal, central, or rear region of the wedge depending on the erosion period and the weakening. Erosion at slopes slightly above or below the critical value results in exhumation toward the foreland or the hinterland, respectively, regardless of the erosion period. Exhumation is associated with duplexes, imbricate fans, antiformal stacks, and major backthrusting. Comparisons with sandbox experiments confirm that the thickness, dips, vergence, and exhumation of thrust sheets can be reproduced with friction and erosion parameters within realistic ranges of values.